FORM OF LEGAL PROTECTION FOR EMPLOYERS AND WORKERS DURING THE PROCESS OF RESOLVING DISPUTES TERMINATION OF EMPLOYMENT - Syafii Syafii; M. Zamroni; Sudjiono Sudjiono (Jurnal Reformasi Hukum : Cogito Ergo Sum, 2020)
This research was created to determine the form of legal protection for employers and workers during the process of resolving disputes termination of employment. This study uses a positive legal literature study on employment using a deductive-inductive approach and emphasizes on reality (law in action). The results showed a form of legal protection for employers and workers during the process of termination of employment consists of prevention (preventive) which in the context of the process of resolving disputes termination of employment is a concrete effort of the state in providing guarantees to human rights in the right of association and the right to negotiate together by providing opportunities to the parties who are disputing in terms of termination of employment relationships to conduct bipartite negotiations aimed at preventing the termination of employment in ways that can be agreed by both parties and can be carried out without anyone feeling harmed and justified by the law and repressive settlement in the process of resolving termination of employment disputes is the arrangement of settlement procedures arranged in such a way as to ensure equal opportunities upfront in law and fair treatment in employment relationships,  whose concrete form is termination of employment without or not obtaining determination from the institution of settlement of industrial relations disputes is null and void, which results in the deletion of all or part of the matter related to termination of employment so that the employment relationship continues and all rights and obligations for the parties remain in force that must remain in force as long as it has not obtained a determination from the institution of settlement of industrial relations disputes until the decision or determination of a permanent legal force (inkraht van gewijsde)